Secretarial Students' Preferences of Learning Materials - Wawan Hendrawan (Jurnal Sekretaris dan Administrasi Bisnis, 2017)
Successful learning outcomes are determined by the best learning materials forging the students' profiles after graduation. To this end, it is imperative for lecturers or teachers conducting a study in accordance to the issue of learning materials. This research is not the exception. It tries to investigate the students' preferences of the learning materials used. This study is performed inside the language laboratory in one academy of secretary located in the heart of Bandung City, West Java, Indonesia. There are thirty seven students, all of them are women, from two different classes participating in this study. They are fourth semester students taking the English listening skill course which followed by them for sixteen sessions. This study uses a mix method as its approach with case study as its design. The instrument of data collection is questionnaire. The data taken from this study is analysed quantitatively and qualitatively. The results demonstrate that first audio-video becomes the most preferred form of learning material. By this, it brings its own implication like learning is more real, motivating and enjoyable. Second, the use of different forms of learning material would harvest various end goals. Third, for secretaries, the goal of learning English is the proficiency of using the four language skills. Finally, this research opens the way to the understanding of the preferences of students while learning English listening skill course in an academy of secretary. Keywords: secretary, learning materials, learning goals